PERAN DEWAN PENGAWAS SYARIAH DALAM MEMIPLEMENTASIKAN AKAD SYARIAH: KASUS DI KSPPS BONDHO BEN TUMOTO GUNUNGPATI SEMARANG - Ubed, Ubbadul Adzkiya; Uswatun Hasanah; Ali Imron; Imam Khoirul Ulumuddin (Jurnal Pendidikan Nusantara, 2021)
The focus in this research is the monitoring mechanism of the implementation of sharia contracts, optimizing the role of DPS in KSPPS. The purpose of this study is to describe: the monitoring mechanisms performed by DPS, how to optimize the role of DPS, the factors that influence the supervision of DPS at KSPPS Bondho Ben Tumoto Gunungpati Semarang. This research was conducted using qualitative methods and descriptive approaches. The data collection technique was done by interview, observation, and documentation. Analysis of data collection using data reduction, and data presentation. The conclusion of the study shows: the supervisory mechanism carried out by DPS is active / monitoring and passive supervision, the factors that influence supervision are the understanding of the community regarding the sharia economy and the facilities provided by the cooperative to DPS, and optimization will be achieved if the factors affecting supervision are maximally fulfilled.